Long and Short Shelf Life Foods in Consumer Purchasing Decisions – The Case of Poland - Urszula SAMOTYJA; Magdalena ANKIEL (Communications of International Proceedings, 2020)
Identifying consumer behavior related to the consumption of long and short shelf life foods as well as recognizing consumer preferences regarding purchases of food with different shelf life dates is important for effectively tackling the goals of sustainable development. In the article, the authors presented the results of a study on consumer behavior on the food market in Poland, with particular emphasis on preferences in the purchase of perishable and shelf-stable food with long and short shelf life dates. The research method used was a direct individual questionnaire interview; the surveyed population constituted of consumers purchasing food products (N = 1145). The results of the study indicate that in the case of shelf-stable foods, consumers prefer the ones with a long shelf life, and in the case of fresh food, consumers prefer the ones with a short shelf life. Moreover, consumers in Poland are characterized by a positive attitude towards discounted food with a short shelf life, only if they are convinced that they will manage to consume it on time. The research conclusions are a contribution to the discussion on the relationship between consumer preferences in the studied area and their handling of purchased food with short shelf lives in the context of sustainable development and reducing food waste. This study was supported by the National Science Centre (Narodowe Centrum Nauki), Poland [grant number 2017/27/B/HS4/00805].
Keywords: Consumer Behavior; Purchase Decisions; Food Labelling; Shelf life Labelling; ‘Use By’ Date; ‘Best Before’ Date; Food Waste.